Genotype-phenotype correlations in SCN8A-related disorders reveal prognostic and therapeutic implications - Johannesen, Katrine M; Liu, Yuanyuan; Koko, Mahmoud; Gjerulfsen, Cathrine E; Sonnenberg, Lukas; Schubert, Julian; Fenger, Christina D; Eltokhi, Ahmed; Rannap, Maert; Koch, Nils A; Lauxmann, Stephan; Krüger, Johanna; et al. (Brain, 2022)
We report detailed functional analyses and genotype-phenotype correlations in 392 individuals carrying disease-causing variants in SCN8A, encoding the voltage-gated Na+ channel Nav1.6, with the aim of describing clinical phenotypes related to functional effects. Six different clinical subgroups were identified: Group 1, benign familial infantile epilepsy (n = 15, normal cognition, treatable seizures); Group 2, intermediate epilepsy (n = 33, mild intellectual disability, partially pharmaco-responsive); Group 3, developmental and epileptic encephalopathy (n = 177, severe intellectual disability, majority pharmaco-resistant); Group 4, generalized epilepsy (n = 20, mild to moderate intellectual disability, frequently with absence seizures); Group 5, unclassifiable epilepsy (n = 127); and Group 6, neurodevelopmental disorder without epilepsy (n = 20, mild to moderate intellectual disability). Those in Groups 1-3 presented with focal or multifocal seizures (median age of onset: 4 months) and focal epileptiform discharges, whereas the onset of seizures in patients with generalized epilepsy was later (median: 42 months) with generalized epileptiform discharges. We performed functional studies expressing missense variants in ND7/23 neuroblastoma cells and primary neuronal cultures using recombinant tetrodotoxin-insensitive human Nav1.6 channels and whole-cell patch-clamping. Two variants causing developmental and epileptic encephalopathy showed a strong gain-of-function (hyperpolarizing shift of steady-state activation, strongly increased neuronal firing rate) and one variant causing benign familial infantile epilepsy or intermediate epilepsy showed a mild gain-of-function (defective fast inactivation, less increased firing). In contrast, all three variants causing generalized epilepsy induced a loss-of-function (reduced current amplitudes, depolarizing shift of steady-state activation, reduced neuronal firing). Functional effects were known for 170 individuals. All 136 individuals carrying a functionally tested gain-of-function variant had either focal (n = 97, Groups 1-3) or unclassifiable (n = 39) epilepsy, whereas 34 individuals with a loss-of-function variant had either generalized (n = 14), no (n = 11) or unclassifiable (n = 6) epilepsy; only three had developmental and epileptic encephalopathy. Computational modelling in the gain-of-function group revealed a significant correlation between the severity of the electrophysiological and clinical phenotypes. Gain-of-function variant carriers responded significantly better to sodium channel blockers than to other anti-seizure medications, and the same applied for all individuals in Groups 1-3. In conclusion, our data reveal clear genotype-phenotype correlations between age at seizure onset, type of epilepsy and gain- or loss-of-function effects of SCN8A variants. Generalized epilepsy with absence seizures is the main epilepsy phenotype of loss-of-function variant carriers and the extent of the electrophysiological dysfunction of the gain-of-function variants is a main determinant of the severity of the clinical phenotype in focal epilepsies. Our pharmacological data indicate that sodium channel blockers present a treatment option in SCN8A-related focal epilepsy with onset in the first year of life.
Keywords: Seizures; SCN8A; Epileptic Syndromes; Sodium Channel Blockers; Infant; Humans; genetické asociační studie; kojenec; mutace; záchvaty; genetics; epilepsie generalizovaná; lidé; Epilepsy, Generalized; mentální retardace; blokátory sodíkových kanálů; Intellectual Disability; epilepsy; napěťově řízený sodíkový kanál, typ 6; Genetic Association Studies; prognóza; personalized medicine; epileptické syndromy; Mutation; Prognosis; NAV1.6 Voltage-Gated Sodium Channel